Recent Contact Features in Northwest Papuan Malay - David Gil (Nusa, 2023)
This paper presents an exploration of language contact between a subvariety of Papuan Malay spoken in the Bird's Head and Cenderawasih Bay regions, and other languages of the region, both Austronesian and non-Austronesian. Seven case studies are provided of features that have recently entered Northwest Papuan Malay due to contact with local languages: (a) dual-number pronouns; (b) pronouns marking person in Noun-Phrases; (c) pronouns forming discontinuous associative inclusories; (d) frequent use of pronouns; (e) null ‘give’; (f) frequent use of null content interrogatives; and (g) Janus-faced Instrumental verbal marking with serial verb pake ‘use’. Such instances of contact-induced change are best understood as reflecting the adoption, by speakers of Papuan Malay, of an indigenous linguistic perspective, determining not just grammaticality but also idiomaticity, or ways of saying things".